Evidence for Contribution of Neutral Trehalase in Barotolerance of Saccharomyces cerevisiae - Iwahashi, Hitoshi (American Society for Microbiology, 2000)
In yeast, trehalose accumulation and its hydrolysis, which is catalyzed by neutral trehalase, are believed to be important for thermotolerance. We have shown that trehalose is one of the important factors for barotolerance (resistance to hydrostatic pressure); however, nothing is known about the role of neutral trehalase in barotolerance. To estimate the contribution of neutral trehalase in resisting high hydrostatic pressure, we measured the barotolerance of neutral trehalase I and/or neutral trehalase II deletion strains. Under 180 MPa of pressure for 2 h, the neutral trehalase I deletion strain showed higher barotolerance in logarithmic-phase cells and lower barotolerance in stationary-phase cells than the wild-type strain. Introduction of the neutral trehalase I gene (NTH1) into the deletion mutant restored barotolerance defects in stationary-phase cells. Furthermore, we assessed the contribution of neutral trehalase during pressure and recovery conditions by varying the expression of NTH1 or neutral trehalase activity with a galactose-inducible GAL1 promoter with either glucose or galactose. The low barotolerance observed with glucose repression of neutral trehalase from the GAL1 promoter was restored during recovery with galactose induction. Our results suggest that neutral trehalase contributes to barotolerance, especially during recovery.